Peranan Kepala Persekutuan Hukum Adat Sebagai Mediator Di Negeri Hutumuri Dalam Penyelesaian Sengketa Jual Beli Tanah Dati - Waelaruno, Glen Jantje; Mustamu, Julista; Matitaputty, Marlien Irene (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The presence of Law Number 30 of 2014 concerning Government Administration which consists of 89 articles is intended to create an orderly administration of Government Administration, create legal certainty, prevent abuse of authority, ensure the accountability of Government Agencies and/or Officials, provide legal protection to citizens and the apparatus. the government implements the provisions of laws and regulations and applies the General Principles of Good Governance (AUPB), and provides the best possible service to the citizens. the concept of the rule of law, the concept of state institutions and government institutions, the concept of authority and the concept of good government. Purposes of the Research: This study aims to describe APIP's authority in the PDAM corruption case in Saumlaki and to find out the legal consequences of the abuse of authority by APIP in the PDAM corruption case in Saumlaki.Methods of the Research : This method used is a normative juridical, with a statutory approach and a conceptual approach, and uses the concept of the rule of law, the concept of state institutions and government institutions, the concept of authority and the concept of good government.Results/Findings/Novelty of the Research: The results of the study show that there are several criteria in determining state losses, if the case is simple, the determination of the value of state losses is carried out by the Prosecutor's Office itself. On the other hand, if the case needs an in-depth audit, the Attorney General's Office will coordinate with the Supreme Audit Agency. The statutory statement does not clearly state the name of the institution that is authorized to declare the value of state losses, so there is uncertainty when determining the institution as the auditor for state losses of BPK/BPKP.